2017
DOI: 10.4102/jomped.v1i1.25
|View full text |Cite
|
Sign up to set email alerts
|

<i>Dryopteris filix-mas</i> (Dryopteridaceae) leaves inhibit mouse uterine activity

Abstract: Background: The plant Dryopteris filix-mas has been used traditionally for its uterine-stimulant effects.Aim: The current study is therefore aimed at investigating and determining the effect of the leaves of D. filix-mas on uterine contractility in vitro.Setting: Fresh leaves of D. filix-mas were collected from a river bank in the south-western part of Nigeria.Methods: The leaves of D. filix-mas were cleaned, dried and extracted in methanol. The extract (0.07 µg/mL–21.0 µg/mL) was tested on the isolated mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…After third stage the rough filtration through lavsan filters was carried out followed by precipitation of suspended particles for 15 min at 4500 rpm (centrifuge VS-1536E) and final filtration through SF paper (slow filtration). Obtained extract was separated into two equal volume parts and dried under reduced pressure in vacuum rotary evaporator IR-1LT (15 mmHg, 25℃) to full remove of extragent [13,14].…”
Section: Preparation Of Aqueous-ethanolic Extracts Of Roots and Rhizo...mentioning
confidence: 99%
See 1 more Smart Citation
“…After third stage the rough filtration through lavsan filters was carried out followed by precipitation of suspended particles for 15 min at 4500 rpm (centrifuge VS-1536E) and final filtration through SF paper (slow filtration). Obtained extract was separated into two equal volume parts and dried under reduced pressure in vacuum rotary evaporator IR-1LT (15 mmHg, 25℃) to full remove of extragent [13,14].…”
Section: Preparation Of Aqueous-ethanolic Extracts Of Roots and Rhizo...mentioning
confidence: 99%
“…The content of kaempferol-3-O-glucoside was determined by HPLC method using standard [15]. The amount of filixic acid was proved by combine method with use of HPLC, NMR С 13 and H 1 [18]. Phytochemical characteristics of obtained extracts are shown in Table 1.…”
Section: Preparation Of Aqueous-ethanolic Extracts Of Roots and Rhizo...mentioning
confidence: 99%
“…Previous studies have found that it possesses antihelmintic activity (Urban et al, 2014), antimicrobial activity (Mandal andMondal, 2014), antidiarrheal (Uwumarongi et al, 2016), uterine relaxant (Bafor et al, 2017) and anti-inflammatory (Erhirhie et al, 2019) activities. A preliminary study by Sekender et al, (2012) revealed that it possesses anti-oxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Its leaves are bipinnated and consist of 20-35 pinnae on each side of the rachis (Fig 1). Its stalks are covered with orange-brown scales (Bafor et al, 2017). The leaf decoction is ethno medicinally used in rheumatoid arthritis, wounds, bleeding disorders, ulcers, worm infestation and malaria (Tagarelli et al, 2010;Erhirhie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of the global population, particularly those of rural settlements, depend on medicinal plants in various forms as medicines for the maintenance of their health [11]. In the Western countries with highly developed health care systems, phytotherapy is considered as a part of complementary and Alternative Medicine (CAM) and it has significantly increased in recent years [12]. Globally, the use of medicinal plants for childcare and general well-being has long been recognized.…”
Section: Introductionmentioning
confidence: 99%